Equity and administration - Turner, P. G. ca. 20./21. Jh (Cambridge University Press, 2016)
"Each generation of lawyers in common law systems faces an important question: what is the nature of equity as developed in English law and inherited by other common law jurisdictions? While some traditional explanations of equity remain useful - including the understanding of equity as a system that qualifies the legal rights people ordinarily have under judge-made law and under legislation - other common explanations are unhelpful or misleading. This volume considers a distinct and little noticed view of equity. By examining the ways in which courts of equity have addressed a range of practical problems regarding the administration of deliberately created schemes for the management of others' affairs, modern equity can be seen to have a strongly facilitative character. The extent and limits on this characterisation of equity are explored in chapters covering equity's attitude to administration in various public and private settings in common law systems"...
Keywords: LAW / Civil Law; Equity -- Great Britain; Equity; Großbritannien